Measures against the financing of “lone wolves” and small terrorist cells in Europe - Svetoslav YORDANOV (Bulletin of "Carol I" National Defense University)
This article examines the modern trends of radicalization and terrorism and researches the contemporary sources and methods of terrorist financing. The paper focuses on the emergence of new risks and threats to the European security system, such as the activity of “lone wolves” and small terrorist cells. The purpose of the publication is to study the financing mechanisms of small independent terrorist organizational units and to propose measures against them.